An Examination about "Focal Point" and "Scope” in Needs Analysis on Language Education - Sönmez, Hülya (My University, 2020)
In this study, the focal point and scope characteristics of these studies during need assessment were determined examining studies on language education. Since the focal point specifies the source of the needs in the process of determining needs, it can be associated with the individual (student and teacher). The scope implies the purpose of the language learning process. For this reason, it is possible to relate the scope to the why question. Based on these two factors, it is aimed to present a different perspective in the process of determining the needs of language education in this research. The general survey model was used. The data collected by the general survey model were examined via the descriptive analysis method. According to the findings, it was determined that students' and teachers' needs should be brought to the forefront in the process of determining the contents. Particularly while preparing the content, it is necessary to focus on two aspects. The first aspect is how the content will be transformed according to the learners' needs. The second aspect is how to transfer the contents depending on the teachers’ needs. Therefore the elements of education should be updated depending on the learner's needs and teacher's needs in the educational process. Because the learners' and teachers' needs are equally important. Based on this fact, the relationship between focal point and scope in education needs to be examined in more detail.

Bu çalışmada dil eğitimiyle ilgili çalışmalar incelenerek bu çalışmaların ihtiyaç değerlendirme sürecindeki odak noktası ve kapsam özellikleri belirlenmiştir. Odak noktası, ihtiyaçları belirleme sürecinde ihtiyaçların kaynağını göstermesi itibariyle bireyle (öğrenci ve öğretmen) ilişkilendirilebilir. Kapsam ise dil eğimindeki amacı ifade eder. Bu nedenle, kapsamı neden sorusuyla ilişkilendirmek mümkündür. Bu iki faktörden hareketle araştırmada ihtiyaçların belirlenmesi sürecinde farklı bir bakış açısının sunulması amaçlanmaktadır. Çalışmada genel tarama modeli kullanılmıştır. Genel tarama modeline uygun olarak toplanan veriler, betimsel analiz yöntemiyle incelenmiştir. Ulaşılan bulgulara göre içeriklerin belirlenmesi sürecinde öğrencilerin ve öğretmenlerin ihtiyaçlarının ön plana çıkarılması gerekir. Bu kapsamda içeriği hazırlarken iki konuya odaklanmak gerekiyor. Birincisi, içeriğin öğrencilerin ihtiyaçlarına göre nasıl verileceğidir. İkinci boyut, öğretmenlerin ihtiyaçlarına göre içeriğin nasıl aktarılacağıdır. Bu nedenle eğitim unsurları, öğrenenlerin/öğretmenlerin ihtiyaçlarına göre eğitim sürecinde sürekli güncellenebilmedir. Çünkü öğrencilerin ihtiyaçları ve öğretmenlerin ihtiyaçları aynı derecede önemlidir. Bu gerçeğe bağlı olarak eğitimde odak noktası ile kapsam arasındaki ilişkinin daha detaylı incelenmesi gerekir.
Dil Eğitimi ile İlgili İhtiyaç Analizinde "Odak Noktası" ve "Kapsam" Üzerine Bir İnceleme